Karakteristik dan Motivasi Augmentasi Penis dengan Komplikasinya di RSUP Prof. Dr. R. D. Kandou dan RS Jejaring - Purba, Adrian; Astram, Ari; Monoarfa, Richard (UNIVERSITAS SAM RATULANGI, 2018)
Abstract: Penile augmentation is an individual effort to enlarge one’s penile size for his sexual satisfaction and his mate without functional alteration. This study was aimed to obtain the profile of motivation, sexual satisfaction, mental distortion, and complications in patients with penile augmentation. This was a descriptive categorical study with a retrospective approach. This study was conducted at Prof. Dr. R. D. Kandou Hospital and its link hospitals for 10 months involving 23 patients; most of them (34.78%) were 26-35 years old. Most patients (61%) had internal motivation based on NSSS scale >30. Based on ulcer free period, 3 patients had free period of ulcer I; no patient had free period of ulcer II. Based on pain scale, 14 patients (60.87%) had pain scale of <5 and 9 patients (39.13%) had pain scale of >5. Most complications were in the form of ulcers located in preputium (56.52%). The relationships between motivation and NSSS scale before and after penile augmentation were analyzed using Fisher exact test which obtained P = 0.000 for relationship between motivation and NSSS scale (sexual satisfaction) before and after penile augmentation and P = 0.360 between post augmentation (with its complications) and sexual satisfaction. Conclusion: Patients with penile augmentation were internally and externally motivated without any mental distortion. There was a significant relationship between internal motivation and penile augmentation as well as between motivation and sexual satisfaction. Albeit, there was no significant relationship bewteen complications of penile augmentation and sexual satisfaction. Most patients suffered complications.Keywords: penile augmentation, NSSSAbstrak: Augmentasi penis merupakan usaha individu untuk membesarkan ukuran penis demi memenuhi hasrat seksual dan pasangannya tanpa perubahan fungsi. Penelitian ini bertujuan untuk mendapatkan gambaran motivasi, kepuasan seksual, adanya gangguan jiwa, dan komplikasi pada pasien yang melakukan augmentasi penis. Jenis penelitian ialah deskriptif kategorik dengan pendekatan retrospektif. Penelitian ini dilakukan di RSUP Prof. Dr. R. D. Kandou dan RS jejaring selama 10 bulan yang melibatkan 23 pasien. Rentang usia pasien 16-59 tahun, terbanyak pada usia 26-35 tahun (34,78%). Sebagian besar pasien (61%) dengan motivasi secara internal berdasarkan skala NSSS>30. Berdasarkan periode bebas ulkus didapatkan 3 pasien dengan periode bebas ulkus I; tidak didapatkan pasien dengan periode bebas ulkus II. Berdasarkan skala nyeri didapatkan 14 pasien (60,87%) dengan skala nyeri <5 dan 9 pasien (39,13%) dengan skala nyeri >5. Lokasi komplikasi terbanyak berupa ulkus di preputium (56,52%). Analisis menggunakan Fisher exact terhadap hubungan motivasi dan skala NSSS sebelum dan sesudah augmentasi penis memper-lihatkan hubungan antara motivasi dan kepuasan seksual dengan nilai P = 0,000 (<0,05) serta hubungan antara pasca augmentasi (beserta komplikasi) dan kepuasaan seksual dengan nilai P = 0,360 (>0,05). Simpulan: Pasien yang melakukan augmentasi penis termotivasi secara internal dan eksternal tanpa adanya distorsi gangguan psikiatrik. Terdapat hubungan bermakna antara motivasi internal dan augmentasi penis serta antara motivasi melakukan augmentasi penis dan kepuasan seksual. Tidak terdapat hubungan bermakna antara komplikasi augmentasi penis dan kepuasaan seksual. Hampir seluruh pasien disertai komplikasi.Kata kunci: augmentasi penis, NSSS